Pengembangan Sistem Informasi Penanganan Keluhan Warga Desa Berbasis Web (Studi Kasus Pemerintah Desa Suwayuwo) - Muhammad Ikhlas Dermawan; Ismiarta Aknuranda; Widhy Hayuhardhika Nugraha Putra (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2019)
Suwayuwo Village is located in Kecamatan Sukorejo, Kabupaten Pasuruan, East Java. The Suwayuwo Government opened a complaint handling to service complaints from residents of Suwayuwo Village on services from the village government. However, the lack of maximum complaints handling services has caused complaints from villagers not to be recorded properly. Based on these problems, information system is required through developing complaint handling information system. Information system development are carried out through business process modelling, requirements analysis, design and implementation of complaint handling information system by applying object-oriented approach. Furthermore, system testing are carried out to find out which system could run according the requirements that have been identified. Business process modelling activities generate As-Is and To-Be business process model. The requirement analyis generate functional requirement, non fuctional requirement, and visualisation of system capabilities use case diagram. The results of system design are object model documentation within class diagram, object interaction model within sequence diagram, database design, algorithm design and user interface design.The implementation result is a Web-based complaint handling Information system. The result of system testing shows that system could run according previous identified requirement.